Recent Synthetic Applications of the Hypervalent Iodine(III) Reagents in Visible-Light-Induced Photoredox Catalysis - Chen, Chaoyue; Wang, Xin; Yang, Tinghai (Frontiers in Chemistry, 2020)
The synergistic combination of visible-light-induced photoredox catalysis with hypervalent iodine(III) reagents (HIRs) represents a particularly important achievement in the field of hypervalent iodine chemistry, and numerous notable organic transformations were achieved in mild and environmentally benign fashion. This account intends to summarize recent synthetic applications of HIRs in visible-light-induced photoredox catalysis, and they are organized in terms of the photochemical roles of HIRs played in reactions.